PENGARUH FAKTOR-FAKTOR RIIL EKONOMI TERHADAP PDRB PERTANIAN INDONESIA - Tarmizi Abbas; Nurhayati M (LPPM Universitas Malikussaleh – Indonesia, 2021)
This study analyzed the effects of government expenditure, investment, and labor on the Gross Regional Domestic Product (GRDP) of the agricultural sector in all provinces in Indonesia using panel data for four years (2015 - 2018). The model used was a Panel Data Regression. The results showed that Government Expenditure, Investment positively influenced, and Labor negatively influenced the GRDP of the Agricultural Sector, and these three variables significantly influenced the GRDP of the Agricultural Sector in Indonesia.